Metro, 23 Mei 2011 - Yusri Abdul Malek; Asmah Rusman; Hayati Ibrahim; Mohamad Apendy Ishak; Mohd Husni Mohd Noor; Muhammad Hafiz Nawawi; Nurhidayu Razali; Nurul Ekhwan Haque Fazlul Haque; Raja Noraina Raja Rahim; Siti A'isyah Sukaimi; Zaitie Satibi (The New Straits Times Press (M) Bhd, 2011)
"Saya tarik tangan adik ketika kami lari menyelamatkan diri, tapi kaki adik tersangkut pada besi khemah dan dia jatuh.